14 Quality improvement standards to prevent inappropriate use of colonoscopy in australian healthcare services. (4th December 2019) - Duggan, Anne; Bhasale, Alice; Abbenbroek, Brett
Abstract : Most colonoscopy in Australia is carried out for the purpose of bowel cancer detection or prevention. Australia has a well-established national bowel cancer screening program based on faecal occult blood testing, with lower rates of mortality and advanced cancer diagnosis seen in participants. 1 Strong evidence supports the use of colonoscopy for bowel cancer screening or surveillance in high-risk individuals. However, most colonoscopy procedures do not arise as a result of the National Bowel Cancer Screening program and both overuse and underuse are evident, contrary to both the epidemiology of bowel disease and evidence-based guidelines. 2 Medical Benefits Schedule reimbursed diagnostic colonoscopy, with and without polypectomy, increased respectively by 177% and 51% between 2004 and 2015. It is estimated that for every 1 million Australians aged 50 years and over, 80, 000 people at average risk of bowel cancer are being over-screened with colonoscopy and 29, 000 people at increased risk are not having the colonoscopy they need. 2 Overuse of the procedure also makes it harder for patients in greatest need to access care with 75% of colonoscopies being carried out in private hospitals, while only 50% of Australians have private health insurance. Although the risk of complications is low, inappropriate use increases exposure to potential harms including perforation, sedation-related complications and adverse patient experience, reducing future participation in screening. The Australian Commission on Safety and Quality in Health Care developed the Colonoscopy Clinical Care Standard to define minimum requirements for high quality colonoscopy care. The standard reflects current guidelines and addresses primary care, clinical referral, bowel preparation, sedation, colonoscopist certification, patient-centred care, and evidence-based surveillance. Shared decision-making and fully informed financial and procedural consent are emphasised. Quality indicators are specified for colonoscopy care that are equivalent to the indicators required for ongoing recertification of colonoscopists. All acute hospitals and day procedure services are required to demonstrate implementation of the colonoscopy standard when undergoing mandatory accreditation to the National Safety and Quality Health Service (NSQHS) Standards. Implementation of the standard was piloted in two public hospitals, a private hospital and a day procedure unit from May to August 2019, including a simulated accreditation against the NSQHS Standards. While quality improvement programs exist in other countries, the Colonoscopy Clinical Care Standard represents an integrated approach to national health service accreditation to improve quality and safety and address inappropriate colonoscopy use. References: Australian Institute of Health and Welfare 2018. Analysis of bowel cancer outcomes for the National Bowel Cancer Screening Program: 2018. Cat. no. CAN 113. Canberra: AIHW. Australian Commission on Safety and Quality in Health Care and Australian Institute of Health and Welfare. The third Australian atlas of healthcare variation. Sydney: ACSQHC, 2018.